INTRATHECAL CHEMOTHERAPY FOR CANCERAMOTOSIS OF THE BRAIN MININGS. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Previously, carcinomatosis of the meninges of the brain and spinal cord was considered a rare manifestation of metastatic disease. However, leptomeningeal disease is now becoming increasingly evident as many drugs do not reach sufficient concentrations in the cerebrospinal fluid to act on tumor cells, and the number of patients is increasing due to increasing life expectancy with modern treatment [1–3]. Carcinomatosis of the meninges of the brain or spinal cord is an unfavorable factor and is associated with a poor prognosis